PROFILING THE DIGITAL LITERACY OF SENIOR HIGH SCHOOL STUDENTS IN AN ISLAMIC BOARDING SCHOOL IN EAST JAVA - Lutfi Saksono; Syafi'ul Anam; Abdul Hafidz; Muhamad Sholeh; Nanin Verina Widya Putri; Muhammad Farid Ilhamudin (Institut Pendidikan Tapanuli Selatan, 2022)
This study aimed to investigate the digital literacy of senior high school students in an Islamic boarding school in East Java, Indonesia. Four questions guided the inquiry in this study: 1) to what extent is the students’ digital literacy? 2) how is the students’ view toward the use of digital technology in learning?;3) what factors affect the use of digital technology by the students?; and 4) from what sources do the students learn digital technology? This study used a quantitative method which involved eighty-one students in senior high school, East Java. The data were collected through a closed-ended questionnaire. Further, the data was analyzed using descriptive statistics aided with SPSS. This study revealed that students had a high level of digital information literacy but a moderate level for language learning. Even though they had a moderate level, they were willing to receive digital literacy instructions for their language learning. They also asserted that the lack of learning materials influenced how the use digital technologies for learning. In addition, they demonstrated that they found new digital literacies mostly from websites and social media. The findings recommended that language teachers adopt new digital literacy that uses digital tools to support teaching and learning to become more effective and creative.